When a Female Pope Meets a Biconfessional Town: Protestantism, Catholicism, and Popular Polemics in the 1630s - Machielsen, Jan (Early Modern Low Countries, 2019)
The early modern afterlife of Pope Joan has been remarkably little studied, perhaps because its contours have seemed familiar: Joan’s existence was embraced by Protestants for its challenge to the apostolic succession of the papacy and rejected by Catholics for the same reason. This role reversal, which cast Protestants as defenders of monastic chronicles and Catholics as their critics, offers ostensible proof for the mercenary use of history in confessional polemics. This article uses an overlooked 1635 defence of the popess, the longest ever written, as a case study to argue the opposite: debates over Pope Joan could be vehicles for popular confessional grievances and identities, and they can teach us much about the difficulties facing the Catholic and Reformed churches in the 1620s and 1630s. Written in Dutch by a German minister of the Church of England, this lengthy treatise possesses a significance well beyond the local conditions – a public disputation in a small biconfessional town in the Duchy of Cleves – that gave rise to its publication.